Biodistribution and trafficking of hydrogel nanoparticles in adult mosquitoes. - Cynthia C H Paquette; Yashdeep Phanse; Jillian L Perry; Irma Sanchez-Vargas; Paul M Airs; Brendan M Dunphy; Jing Xu; Jonathan O Carlson; J Christopher Luft; Joseph M DeSimone; Lyric C Bartholomay; Barry J Beaty (Public Library of Science (PLoS), 2015)
BACKGROUND:Nanotechnology offers great potential for molecular genetic investigations and potential control of medically important arthropods. Major advances have been made in mammalian systems to define nanoparticle (NP) characteristics that condition trafficking and biodistribution of NPs in the host. Such information is critical for effective delivery of therapeutics and molecules to cells and organs, but little is known about biodistribution of NPs in mosquitoes. METHODOLOGY/PRINCIPAL FINDINGS:PRINT technology was used to construct a library of fluorescently labeled hydrogel NPs of defined size, shape, and surface charge. The biodistribution (organ, tissue, and cell tropisms and trafficking kinetics) of positively and negatively charged 200 nm x 200 nm, 80 nm x 320 nm, and 80 nm x 5000 nm NPs was determined in adult Anopheles gambiae mosquitoes as a function of the route of challenge (ingestion, injection or contact) using whole body imaging and fluorescence microscopy. Mosquitoes readily ingested NPs in sugar solution. Whole body fluorescence imaging revealed substantial NP accumulation (load) in the alimentary tracts of the adult mosquitoes, with the greatest loads in the diverticula, cardia and foregut. Positively and negatively charged NPs differed in their biodistribution and trafficking. Following oral challenge, negatively charged NPs transited the alimentary tract more rapidly than positively charged NPs. Following contact challenge, negatively charged NPs trafficked more efficiently in alimentary tract tissues. Following parenteral challenge, positively and negatively charged NPs differed in tissue tropisms and trafficking in the hemocoel. Injected NPs were also detected in cardia/foregut, suggesting trafficking of NPs from the hemocoel into the alimentary tract. CONCLUSIONS/SIGNIFICANCE:Herein we have developed a tool box of NPs with the biodistribution and tissue tropism characteristics for gene structure/function studies and for delivery of vector lethal cargoes for mosquito control.